Implications of the California Nurse Staffing Mandate for Other States - Aiken, Linda H.; Sloane, Douglas M.; Cimiotti, Jeannie P.; Clarke, Sean P.; Flynn, Linda; Seago, Jean Ann; Spetz, Joanne; Smith, Herbert L. (Health services research, 2010)
Objectives. To determine whether nurse staffing in California hospitals, where state‐mandated minimum nurse‐to‐patient ratios are in effect, differs from two states without legislation and whether those differences are associated with nurse and patient outcomes. Data Sources. Primary survey data from 22,336 hospital staff nurses in California, Pennsylvania, and New Jersey in 2006 and state hospital discharge databases. Study Design. Nurse workloads are compared across the three states and we examine how nurse and patient outcomes, including patient mortality and failure‐to‐rescue, are affected by the differences in nurse workloads across the hospitals in these states. Principal Findings. California hospital nurses cared for one less patient on average than nurses in the other states and two fewer patients on medical and surgical units. Lower ratios are associated with significantly lower mortality. When nurses' workloads were in line with California‐mandated ratios in all three states, nurses' burnout and job dissatisfaction were lower, and nurses reported consistently better quality of care. Conclusions. Hospital nurse staffing ratios mandated in California are associated with lower mortality and nurse outcomes predictive of better nurse retention in California and in other states where they occur.